Structural Performance of R/C Buildings in 2023 Kahramanmaraş Earthquakes Under the Lens of Hassan Index - Dönmez, Cemalettin; Yildirim, Meltem Eryilmaz; Yesilyurt, Cennet; Gozun, Uveys; Ozturk, Baki; Donmez, Cemalettin (Springer Science and Business Media Deutschland GmbH, 2024)
Starting with the 1999 Kocaeli Earthquake, seismic damage indices have been developed to quantify damage potential. The late Professor Mete Sozen played a significant role in this endeavor by introducing the Hassan Index, which is an indirect measure of the robustness of structures. Its calculation is straightforward, given the vertical structural element dimensions at ground level. Various earthquakes worldwide, from Taiwan to Chile, have provided opportunities to assess its effectiveness across diverse building practices and earthquake characteristics. Following the February 2023 Kahramanmaras Earthquakes, a reconnaissance team was dispatched to gather field data to observe the damages through the lens of the Hassan Index. The study extended to cover all major city and town centers, studying around 250 reinforced concrete buildings with 2-16 stories. These buildings were all constructed after the 2000s. Hence, the data set sheds light on the performance of Turkish construction practices after the commencement of the 1998 Turkish Building code and the following earthquake regulations. By evaluating the newly gathered data alongside the existing dataset, a basis is established to consider the Hassan Index as a preliminary design index rather than solely as a seismic damage index.
Keywords: Damage Index; Earthquake Damage; Reinforced Concrete; Seismic Design